The Role of Social Health and Demographic Factors in Bread Quality: An Ecological Study in Isfahan, Iran. (3rd July 2021) - Amini-Rarani, Mostafa; Abutoraabi, Seyed Haashem; Nosratabadi, Mehdi
Abstract : Social health has been defined as participation in and responsibility for social processes. Because bread is considered an essential staple food in Iran, several social policies have been implemented to improve the quality of bread, regardless of social aspects. The current study aims to investigate the relationship between bread quality, bakers' social health, and demographic factors. This was a cross-sectional ecological study conducted in Isfahan, Iran. Stratified sampling was used to select 171 traditional bakeries from Isfahan's 15 municipality districts. The Adult Social Health Questionnaire was used to collect data. A laboratory test was employed to obtain data on bread quality. The Spearman correlation test, bivariate logistic regression, and multiple logistic regression were applied to analyze the data. The results showed that 36.26% of bakeries had pH ≤ 6 (high-quality bread) and 63.74% of them had pH > 6 (bread quality was low). The use of baking soda had a negative relationship with bakers' social health (P value = 0.029). According to the findings, low social health increased the likelihood of producing low-quality bread by 53% when compared to high social health. Education, specifically illiteracy and semiliteracy, increased the risk of low-quality bread production by 35% and 27%, respectively. Through responsibility, consciousness, and empathy, social health is linked to bread quality. This implies that health policies could be tailored to address the social health of bakeries in order to improve bread quality.